Adsorption and corrosion inhibition properties of cefadroxil on mild steel in hydrochloric acid - Shukla S.K.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Corrosion inhibition of mild steel in 1M HCl by cefadroxil has been studied using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and weight loss methods. The inhibitor showed more than 96% inhibition efficiency at optimum concentration of 11.0×10-4 mol l-1. The results obtained by these techniques were well supported by the atomic force microscopy. Thermodynamic parameters obtained support physical adsorption mechanism and the experimental data fits well into the Langmuir adsorption isotherm model. Potentiodynamic polarization suggests that cefadroxil act as mixed type inhibitor. Thermodynamic parameters suggest the adsorption is spontaneous and exothermic process. The results obtained from the three methods used are in good agreement. © 2011 by ESG.